2020
DOI: 10.1186/s12889-020-08617-5
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of behavioral context and motivational-volitional factors for exercise and sport in adolescence: patterns matter

Abstract: Background: In order to generate more effective interventions to promote exercise and sport in adolescence, a better understanding of the interaction of influencing factors across different levels is needed. In particular, motivation and volition for exercise and sport, as well as the context in which adolescents are doing exercise and sport, have been identified as important factors. Behavioral context refers to both the organizational setting, e.g., doing exercise and sport in a club, and the social setting,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 75 publications
(133 reference statements)
2
20
0
Order By: Relevance
“…Understanding the environmental factors that influence adolescents’ levels of PA during the transition from elementary to secondary school is complex as this study identified a number of intrapersonal and environmental factors that changed during this period. Given our understanding of the environmental factors that influence adolescents’ PA [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 54 , 55 , 56 ], it was not surprising that changes in the school, social, and household environments were highlighted as influencing adolescents’ PA during transition. Studies that examine factors associated with youth PA during the transition from elementary school to secondary school are relatively rare, and this paper addresses an important gap in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Understanding the environmental factors that influence adolescents’ levels of PA during the transition from elementary to secondary school is complex as this study identified a number of intrapersonal and environmental factors that changed during this period. Given our understanding of the environmental factors that influence adolescents’ PA [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 54 , 55 , 56 ], it was not surprising that changes in the school, social, and household environments were highlighted as influencing adolescents’ PA during transition. Studies that examine factors associated with youth PA during the transition from elementary school to secondary school are relatively rare, and this paper addresses an important gap in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Parents play a central role in socializing their adolescents to PA opportunities, and this process starts when adolescents are young and continuously evolves as they age [ 23 , 24 , 43 , 55 ]. Similar to others, our study found that parents continued to play an important role in supporting adolescent PA [ 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations